Ocular morbidity among children of Baglung, Nepal - Sharma, Dikchhya; Rajak, Ashik; Shrestha, Sabina (Journal of Kathmandu Medical College, 2020)
Background: Development of the visual system occurs during childhood and is completed by eight years of life. Ocular disorders occurring during this period can lead to visual impairment which can have a lifelong impact on the life of the child. Early detection and treatment of ocular problems among children minimizes the risk of visual impairment and amblyopia. Objectives: This study aimed to determine the pattern of ocular morbidity among children attending the health camp in Baglung. Methodology: This was a descriptive cross-sectional study conducted to determine the pattern of ocular morbidity among children in the western region of Nepal, Baglung district. The study was conducted in the month of December 2019 for 2 days after receiving ethical approval. All data obtained were analyzed according to age, sex and pattern of ocular morbidity and were expressed in frequency, percentage and mean as applicable. Convenience sampling technique was used. Results: Five hundred and thirty two children were evaluated in the study. Among them, 143 (26.87%) had ocular morbidity. The mean age of children with ocular morbidity was 9.6± 5.4 years. The total male to female ratio was 1.18:1 and that amongst those with ocular morbidities was seen to be 2.04:1.1. The most common ocular morbidity was refractive error in 43(8.08%) followed by conjunctival in 32(6.01%) and lid disorders in 29(5.45%) respectively. Conclusion: Most of the morbidities observed were either preventable or treatable, therefore, eye health camp is an effective method to identify them.